2017
DOI: 10.1007/s00421-017-3645-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral l-menthol reduces thermal sensation, increases work-rate and extends time to exhaustion, in the heat at a fixed rating of perceived exertion

Abstract: These results indicate that a non-thermal cooling mouth rinse lowered thermal sensation, resulting in an elevated work rate, which extended exercise time in the heat at a fixed RPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
129
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(155 citation statements)
references
References 68 publications
16
129
10
Order By: Relevance
“…In the current study, menthol was swilled intermittently throughout steady‐state exercise and prior to the TTF run. This finding supports previous studies where menthol swilling has shown to improve exercise performance in the heat . Similar to the current study, Jeffries et al found that swilling menthol in the latter stages of an exhaustive cycle improved TTF performance compared with a placebo swill.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, menthol was swilled intermittently throughout steady‐state exercise and prior to the TTF run. This finding supports previous studies where menthol swilling has shown to improve exercise performance in the heat . Similar to the current study, Jeffries et al found that swilling menthol in the latter stages of an exhaustive cycle improved TTF performance compared with a placebo swill.…”
Section: Discussionsupporting
confidence: 93%
“…Menthol is a non‐thermal cooling method therefore does not have an impact on body temperature; however, the current study also found it did not have an effect on perceived thermal sensation, exertion, or thirst. In contradiction, previous studies have associated menthol swilling with improved perceptual ratings in the heat . The lack of impact of menthol swilling on perceptual ratings in the current study could be due to the swilling solution not being cooled (33.4°C), which allowed for the investigation of the solution in a practical scenario where refrigeration was not available.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Menthol mouth swilling is considered a practical ergogenic strategy before and during exercise in hot environments [11,30] and has been used to improve performance during time trials [17,18] and time to exhaustion [16,31]. Perception of menthol mouth swill concentration may be highly individual in nature, with 200 gene variants of the receptor responsible for menthol detection (TRPM8 [32]).…”
Section: Discussionmentioning
confidence: 99%
“…All menthol-containing studies [9,10,[16][17][18][19]31] have employed a repeated exposure during the exercise bout-this is quantified via time or distance. Better understanding the time course of menthol mouth swilling responses, and the potential impact of concentrations upon these, would provide insight into possible limitations in application for menthol-containing strategies.…”
Section: Discussionmentioning
confidence: 99%